2013
DOI: 10.3389/fncel.2013.00177
|View full text |Cite
|
Sign up to set email alerts
|

Anion transport and GABA signaling

Abstract: Whereas activation of GABAA receptors by GABA usually results in a hyperpolarizing influx of chloride into the neuron, the reversed chloride driving force in the immature nervous system results in a depolarizing efflux of chloride. This GABAergic depolarization is deemed to be important for the maturation of the neuronal network. The concept of a developmental GABA switch has mainly been derived from in vitro experiments and reliable in vivo evidence is still missing. As GABAA receptors are permeable for both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 118 publications
0
48
0
1
Order By: Relevance
“…Blocking KCC2 activity should increase intra-cellular [Cl − ] but Viitanen et al (2010) have reported that this change does not influence GABA A receptor-mediated hyperpolarizations and slightly shifts their reversal potential which remains more negative than the resting membrane potential. The lack of meaningful effects on GABA A receptor-mediated hyperpolarizations could be due to the contribution of the Na + dependent anion exchanger (NDAE), which extrudes Cl − and H + and loads and Na + (Payne et al, 2003;Hübner and Holthoff, 2013). Activation of NDAE can promote the inhibitory action of GABA by maintaining Cl − reversal potential negative to the resting membrane potential (Hübner and Holthoff, 2013).…”
Section: Modulation Of Isolated Gabaergic Events By Kcc2 Blockers Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Blocking KCC2 activity should increase intra-cellular [Cl − ] but Viitanen et al (2010) have reported that this change does not influence GABA A receptor-mediated hyperpolarizations and slightly shifts their reversal potential which remains more negative than the resting membrane potential. The lack of meaningful effects on GABA A receptor-mediated hyperpolarizations could be due to the contribution of the Na + dependent anion exchanger (NDAE), which extrudes Cl − and H + and loads and Na + (Payne et al, 2003;Hübner and Holthoff, 2013). Activation of NDAE can promote the inhibitory action of GABA by maintaining Cl − reversal potential negative to the resting membrane potential (Hübner and Holthoff, 2013).…”
Section: Modulation Of Isolated Gabaergic Events By Kcc2 Blockers Andmentioning
confidence: 99%
“…The lack of meaningful effects on GABA A receptor-mediated hyperpolarizations could be due to the contribution of the Na + dependent anion exchanger (NDAE), which extrudes Cl − and H + and loads and Na + (Payne et al, 2003;Hübner and Holthoff, 2013). Activation of NDAE can promote the inhibitory action of GABA by maintaining Cl − reversal potential negative to the resting membrane potential (Hübner and Holthoff, 2013). Although GABA A receptor-mediated signaling remains hyperpolarizing, KCC2 blockers may influence the duration of the pharmacologically isolated GABAergic events by slightly shifting the E GABA and altering the ability of postsynaptic neurons to accumulate Cl − .…”
Section: Modulation Of Isolated Gabaergic Events By Kcc2 Blockers Andmentioning
confidence: 99%
“…The developmental depolarizing-to-hyperpolarizing GABA shift is thought to reflect a developmental decline in intracellular chloride concentration ([Cl -] i ) due to a differential expression/ efficacy of plasmalemmal chloride-accumulating (for example NKCC1 5-7 ) versus chloride-extruding (for example KCC2 (ref. 8) co-transporters 9,10 . By facilitating the generation of action potentials, GABA was further found to promote the generation of patterned network activity 3,[11][12][13][14][15] .…”
mentioning
confidence: 99%
“…Intense GABA A R activation may therefore cause a rapid collapse of the driving force of chloride, but not bicarbonate. This mechanism may mediate GABA A R-dependent depolarization in adult neurons which will result in a further passive chloride load (see Hübner & Holthoff, 2013).…”
Section: Gabaergic Inhibition In the Adult Brainmentioning
confidence: 99%